An extensive analysis of frequency and transient responses in S and C-shaped gears - Yahaya, Saifudin Hafiz; Salleh, Mohd Shukor; Abd Rashid, Mohd Warikh; Abdullah, Abu; Jano, Zanariah; Miura, Kenjiro Takai (Taylor and Francis Ltd., 2022)
Gears are crucial mechanical components and considerably used in consumer and industrial machinery. Gears can be grouped into five types namely spur, helical, rack and pinion, worm and bevel. Spur gear has been selected as a case model in this study mainly because it is one of the basic types of gear which can be easily constructed and fabricated. Spur gear tooth is designed using S and C-shaped transition curves. These curves are constructed using the G2 parametric Said-Ball cubic curve and clothoid templates. The result demonstrates that the C-shaped gear model which consists of the natural frequency of0.7408 Hz and low onaverage and standard deviation of 1.00E-3 mm and 8.072E-3 mm offers the most affordable displacement when compared with S-shaped and existing gear models